Pengimbuhan Ragi Roti dalam Pakan Meningkatkan Respons Imun Nonspesifik dan Pertumbuhan Ikan Nila (SUPPLEMENTATION OF BAKER’S YEAST IN FEED ENHANCE NONSPECIFIC IMMUNE RESPONSE AND GROWTH OF NILE TILAPIA) - Manoppo, Henky; Kolopita, Magdalena EF (Jurnal Veteriner, 2015)
A study was carried out to evaluate the efficacy of Baker’s yeast (Saccharomyces cereviciae) to enhancenonspecific immune response and growth of Nile tilapia fish (Oreochromis niloticus). The fish were obtainedfrom Freshwater Hatchery Tateli (BP3I), Marine and Fisheries Office, North Sulawesi. After acclimatizationfor two weeks in 1000 L fiberglass tank, fish with an average weight of 9 g were put in five 45 L-aquaria ata density of 15 fish/aquarium. During the experiment, fish were fed with feed pellet supplemented withfive different doses of baker’s yeast (10, 20, 30, 40 g yeast/kg pellet) for four consecutive weeks at 5% bw/day, twice a day. Fish in different aquarium received different dose of baker’s yeast. Immune parametersincluding total leucocyte count and phagocytosis activity and growth of fish were measured at two weeksinterval. After four weeks of feeding, total leucocyte count and phagocytosis activity of phagocyte cells offish fed pellet supplemented with 10 g yeast/kg pellet increased significantly as compared to that ofcontrol fish (p<0.01). Growth of fish fed pellet supplemented with 10 g yeast/kg pellet also increasesignificantly as compared to control group (p=0.01). Average weight gain of fish fed pellet supplementedwith 10 g yeast/kg pellet was 15.00±1.00 g while control fish was 8.33 g. As conclusion, supplementationof baker’s yeast in feed could enhance nonspecific immune response and growth of Nile tilapia fish.
Keywords: Saccharomyces cereviciae, nonspecific immune response, total leucocyte count, phagocytosis activity, Oreochromis niloticus